THE EFFECTIVENESS OF PICTURE SERIES TOWARD SPEAKING (An Experimental Research At Eleventh Grade Of SMK Pemuda Taruna Ngraseh Bojonegoro) - Iin Widya Lesatri; Ahmad Khudhori; Edi Suwandi (Jurnal Ilmiah Hospitality, 2020)
As one of the basic skill of English, speaking had an important role in language learning process. Speaking was an expression of human being through conversation. Based on observation at SMK Pemuda Taruna Bojonegoro, the researcher found that the students had difficulties in developing ideas that they want to speak. They got difficulties in recalling imagination about something that they wanted to say. To overcome this problem, the researcher tried to apply the technique in teaching speaking English, namely picture series. The research method used in this research was quasi- experimental research. The data collected through pre-test and post-test. The sample of the research was the eleventh grade students of SMK Pemuda Taruna Ngraseh. The resulf of the data indicated that, there was difference between the value of students pre- test and post-test. The mean score of post-test (84,39) was the higher than the score obtained in the pre-test (39,45). From t-count , the researcher found that, the value of t- count (-42,698) was higher than t-table (-47,191) at the level of significance 0,000 degree of freedom (df) = 17 . Based on the findings, the researcher concluced that, the use of picture series had good improvement for students’ speaking skill at SMK Pemuda Taruna Ngraseh.